2023
DOI: 10.1021/acs.langmuir.3c00667
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Organic Frameworks Facilitate Nucleic Acids for Multimode Synergistic Therapy of Breast Cancer

Abstract: Compared with traditional medical methods, gene therapy and photodynamic therapy are the new fields of cancer treatment, and they more accurately and effectively obtain preferable therapeutic effects. In this study, a chemotherapy drug-free nanotherapeutic system based on ZIF-90 encapsulated with Ce6-G3139 and Ce6-DNAzyme for gene and photodynamic therapies was constructed. Once entering the cancer cell, the therapy system will decompose and release Zn2+, Ce6-G3139, and Ce6-DNAzyme in the acidic environment. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“… Similar to the functional genome contained in the nucleocapsid of a virus, DNAzymes are incorporated into an amorphous Mn/Zn-IP6 nanocapsule that can protect DNAzymes from enzymatic degradation during in vivo circulation. This DNAzyme biocapsule presents multiple prominent features for gene therapy: (i) the negatively charged IP6 protective shell guarantees a long blood circulation time of the developed DNAzyme biocapsule and consequently prevents rapid premature clearance; (ii) the modification with cyclo-(RGDyK) (cRGD) peptides endows with the targeting ability via the specific recognition of α v β 3 integrin receptors overexpressed in the tumor, mimicking the integrin-mediated endocytosis pathway for the cell entry of a virus; , (iii) once the DNAzyme biocapsule is endocytosed, the Mn/Zn-IP6 shell is degraded specifically in response to the acidic lysosomal environment along with the release of DNAzymes and self-supply of a high concentration of Mn 2+ /Zn 2+ , followed by the PEI-triggered lysosomal escape; and (iv) the released DNAzymes together with the self-supplied Mn 2+ /Zn 2+ cofactors specifically catalyze the cleavage of EGR-1 mRNA, ,, inducing the apoptotic death of cancer cells. It is revealed that IP6 significantly inhibits the Bcl-2 expression along with the EGR-1 downregulation, , thereby synergistically enhancing the DNAzyme-mediated gene therapy.…”
mentioning
confidence: 99%
“… Similar to the functional genome contained in the nucleocapsid of a virus, DNAzymes are incorporated into an amorphous Mn/Zn-IP6 nanocapsule that can protect DNAzymes from enzymatic degradation during in vivo circulation. This DNAzyme biocapsule presents multiple prominent features for gene therapy: (i) the negatively charged IP6 protective shell guarantees a long blood circulation time of the developed DNAzyme biocapsule and consequently prevents rapid premature clearance; (ii) the modification with cyclo-(RGDyK) (cRGD) peptides endows with the targeting ability via the specific recognition of α v β 3 integrin receptors overexpressed in the tumor, mimicking the integrin-mediated endocytosis pathway for the cell entry of a virus; , (iii) once the DNAzyme biocapsule is endocytosed, the Mn/Zn-IP6 shell is degraded specifically in response to the acidic lysosomal environment along with the release of DNAzymes and self-supply of a high concentration of Mn 2+ /Zn 2+ , followed by the PEI-triggered lysosomal escape; and (iv) the released DNAzymes together with the self-supplied Mn 2+ /Zn 2+ cofactors specifically catalyze the cleavage of EGR-1 mRNA, ,, inducing the apoptotic death of cancer cells. It is revealed that IP6 significantly inhibits the Bcl-2 expression along with the EGR-1 downregulation, , thereby synergistically enhancing the DNAzyme-mediated gene therapy.…”
mentioning
confidence: 99%